2010
DOI: 10.1080/10426500903436735
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Synthesis of 1-Aminoalkanephosphonic Acid Derivatives from 1-(N-Acylamino)- alkyltriphenylphosphonium Salts

Abstract: Efficient and convenient procedures for the α-amidoalkylation of trialkylphosphites with 1-(N-acylamino)alkyltriphenylphosphonium salts followed by a Michaelis-Arbuzov-type reaction to afford 1-(N-acylamino)alkanephosphonic acid esters have been developed. High yields and simple isolation and purification protocols are the main advantages of this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

7
3

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Recently we developed a simple and effective two-step transformation of N -acyl-α-amino acids into their phosphonic analogues that allows for easy access to a variety of structurally diversified N -acyl-α-aminophosphonates 5 (Scheme 1) [3637]. …”
Section: Resultsmentioning
confidence: 99%
“…Recently we developed a simple and effective two-step transformation of N -acyl-α-amino acids into their phosphonic analogues that allows for easy access to a variety of structurally diversified N -acyl-α-aminophosphonates 5 (Scheme 1) [3637]. …”
Section: Resultsmentioning
confidence: 99%
“…A base (e.g., the Hünig’s base-( i -Pr) 2 EtN) facilitates the cleavage of the C α -P + bond and the formation of corresponding N -acylimine. In turn, the iodide anion (introduced as methyltriphenylphosphonium iodide) enables dealkylation of the intermediate alkoxyphosphonium salt 36 ( Scheme 11 ) [ 50 , 51 , 52 ]. Further studies showed that the reaction could be carried out also under a catalytic-free conditions [ 46 , 52 ].…”
Section: 1-aminoalkyltriarylphosphonium Derivativesmentioning
confidence: 99%
“…Other substrates that have been used in this reaction in the presence of Hünig’s base and methyltriphenylphosphonium iodide as catalysts are diethyl 1-( N -acetylamino)-1-triphenylphosphoniumalkylphosphonate tetrafluoroborates 4 , which can be considered as α-functionalized triphenylphosphonium derivatives of 1-( N -acylamino)alkylphosphonates [ 30 ]. The starting phosphonium salts 4 were synthesized here from diethyl 1-aminoalkylphosphonates readily available from N -acyl-α-amino acids [ 31 , 32 ] by initially subjecting them to electrochemical oxidation to introduce the nucleofugal methoxy group into the α-position, which was followed by nucleophilic substitution of the obtained diethyl 1-( N -acetylamino)-1-methoxyalkylphosphonates with triphenylphosphonium tetrafluoroborate ( Scheme 1 , pathway a). The biggest limitation of this transformation is the electrochemical oxidation step, which was efficiently performed for only two of the simplest models of phosphorus analogs of α-amino acids, namely for the derivative of glycine and alanine, having at the α-position a hydrogen atom or a methyl group, respectively.…”
Section: Introductionmentioning
confidence: 99%